Sosialisasi Kesehatan dan Pola Hidup Sehat bagi Lansia untuk Meningkatkan Kualitas Hidup di Masa Tua - Ahmad Amirul kholid; M. Andon Arifin; Siti Atina Nor Rodziyah (CV. Agrapana Media, 2025)
This community service activity aims to increase the knowledge and awareness of elderly residents in Ngancar Village regarding the importance of maintaining health through the adoption of a healthy lifestyle. The background of this activity is based on the low awareness among the elderly about maintaining both physical and mental health, as well as the high prevalence of degenerative diseases such as hypertension and diabetes, which are often caused by unhealthy lifestyles. The implementation method consisted of three main stages: preparation, socialization, and evaluation. The preparation stage involved coordination with the village government, the local health center (Puskesmas), and elderly health cadres to determine the materials, participants, and technical aspects of the program. The socialization stage was carried out through interactive lectures, discussions, health check-ups, and elderly exercise demonstrations, which were attended by 45 participants. The evaluation was conducted using pre-test and post-test assessments, which showed an average improvement of 28% in participants’ understanding. The results indicated that educational and participatory approaches were effective in enhancing the elderly’s awareness and commitment to practicing healthy living habits sustainably. As a follow-up, the Ngancar Village Elderly Health Group was established to serve as a forum for regular activities such as exercise sessions, routine health check-ups, and nutrition education. In addition, the village government committed to conducting regular elderly health monitoring through the village health program. This activity is expected to serve as a model for sustainable, community-based elderly health empowerment that can be replicated in other regions.